Disc-jet quenching of the galactic black hole Swift J1753.5-0127 - Rushton, A.; Shaw, A.; Fender, R.; Altamirano, D.; Gandhi, P.; Uttley, P.; Charles, P.; Kolehmainen, M.; Anderson, Gemma; Rumsey, C.; Titterington, D. (Oxford University Press, 2016)
We report on radio and X-ray monitoring observations of the BHC Swift J1753.5−0127 taken over a ~10 yr period. Presented are daily radio observations at 15 GHz with the Arcminute Microkelvin Imager Large Array (AMI-LA) and X-ray data from Swift X-ray Telescope and Burst Alert Telescope. Also presented is a deep 2 h JVLA observation taken in an unusually low-luminosity soft-state (with a low disc temperature). We show that although the source has remained relatively radio-quiet compared to XRBs with a similar X-ray luminosity in the hard-state, the power-law relationship scales as ζ = 0.96 ± 0.06, i.e. slightly closer to what has been considered for radiatively inefficient accretion discs. We also place the most stringent limit to date on the radio-jet quenching in an XRB soft-state, showing the connection of the jet quenching to the X-ray power-law component; the radio flux in the soft-state was found to be < 21 μJy, which is a quenching factor of ≥ 25.